Effects of Threat and Motivation on Classical Musicians’ Professional Performance Practice During the COVID-19 Pandemic - López-Íñiguez, Guadalupe; McPherson, Gary E.; Zarza Alzugaray, Francisco J. (Frontiers in Psychology, 2022)
In the past two years our world has experienced huge disruptions because of COVID-19. The performing arts has not been insulated from these tumultuous events with the entire music industry being thrown into a state of instability due to the paralyzing effects of the COVID-19 pandemic. In this study, we examined how classical professional musicians’ ability to cope with uncertainty, economic struggles, and work-life interplay during COVID-19 was influenced by various factors that affect a crucial part of the development and sustainment of music careers: musicians’ practice. We analysed responses to an online survey of 309 classical performing musicians from 41 countries in Europe and Latin America across three pandemic stages: immediately before the pandemic, during the pandemic, and when vaccines were being made available and lockdowns were being reduced or lifted. Structural Equation Modeling indicates relationships between perceptions of threat at the peak of the pandemic and the musicians self- or external-based motivation for the three periods in which respondents were asked to reflect. Findings suggest that musicians who are more internally self-motivated seemed to be more resilient to the pandemic threats and more capable of managing their practicing routines, whereas more externally motivated musicians experienced a reduction in their dedicated time to practice during lockdown. We suggest pedagogical and policy implications, as well as future lines of research that are oriented towards supporting professional musicians in assessing and understanding their motivational drives so that they can cope with situations that disrupt their professional lives.